Pregnancy Desire, Partner Serodiscordance, and Partner HIV Disclosure among Reproductive Age HIV-Infected Women in an Urban Clinic - Corinne M. Rhodes; Susan Cu-Uvin; Aadia I. Rana (Hindawi Limited, 2016)
Women comprise 25% of the US HIV epidemic, with many women of reproductive age. There is a need for providers to address the reproductive needs and desires of women with HIV given that effective antiretroviral therapy has transformed HIV into a chronic disease. This cross-sectional study shows high rates of partner serodiscordance (61%) and moderate HIV disclosure to partners (61%). Patients surveyed reported practitioners discuss condoms (94%) and contraception (71%) more often than pregnancy desire (38%). In our sample, 44% of the surveyed women intended future pregnancy, whereas women who did not intend future pregnancy cited HIV/health and serodiscordance as the most common reasons (56% and 35%, resp.). There was no difference in the knowledge of mother-to-child transmission risk between women who intended or did not intend future pregnancy (p=0.71). These results underline the need for provider training in reproductive counseling to promote risk reduction and education.